1967
DOI: 10.1113/jphysiol.1967.sp008326
|View full text |Cite
|
Sign up to set email alerts
|

A study of cholinoceptive cells in the lateral geniculate nucleus

Abstract: SUMMARY1. The dorsal lateral geniculate nucleus (LGN) of the cat stains densely for acetylcholinesterase, which is present in intra-axonal and extracellular locations.2. Acetylcholine (ACh), cholinomimetic drugs, anticholinesterases and ACh antagonists were administered iontophoretically to neurones in the LGN.3. ACh excited eighty-six of 184 (46.7 %) geniculate neurones and depressed seven (3.8 %).4. The excitatory response to ACh was frequently larger than that to L-glutamate and had a comparable time course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(32 citation statements)
references
References 30 publications
6
26
0
Order By: Relevance
“…LSD and LSD-like drugs do, however, appear to have some effects which are similar to the effects of increasing 5-HT activity in the CNS (Anden et al, 1968(Anden et al, , 1971Fuxe et al, 1972). LSD has frequently been reported to inhibit neurones which 5-HT inhibits (Curtis & Davis, 1962;Phillis, Tebecis & York, 1967;Aghajanian et al, 1972), although the 'mimicking' of 5-HT inhibitory effects by LSD and psychotomimetic tryptamines is not a universal finding (Boakes et al, 1970;present investigation). Nevertheless, mimicking of 5-HT inhibitory effects on neurones in some brain areas may explain some of the actions of these drugs; this possibility is not incompatible with the findings of antagonism of 5-HT excitation in other areas.…”
Section: Discussionmentioning
confidence: 89%
“…LSD and LSD-like drugs do, however, appear to have some effects which are similar to the effects of increasing 5-HT activity in the CNS (Anden et al, 1968(Anden et al, , 1971Fuxe et al, 1972). LSD has frequently been reported to inhibit neurones which 5-HT inhibits (Curtis & Davis, 1962;Phillis, Tebecis & York, 1967;Aghajanian et al, 1972), although the 'mimicking' of 5-HT inhibitory effects by LSD and psychotomimetic tryptamines is not a universal finding (Boakes et al, 1970;present investigation). Nevertheless, mimicking of 5-HT inhibitory effects on neurones in some brain areas may explain some of the actions of these drugs; this possibility is not incompatible with the findings of antagonism of 5-HT excitation in other areas.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, it has been reported that MRF-evoked excitations of long-latency and duration in the lateral geniculate nucleus (Phillis, Tebecis & York, 1967), ventrobasal complex (McCance et al 1968) and the cerebral cortex (Spehlmann & Smathers, 1974) Since the late phase of MRF-evoked inhibition of nucleus reticularis cells is often atropine sensitive and mimics the characteristic burstpromoting properties of ACh on these neurones, we suggest that stimulation of the MRF activates an inhibitory cholinergic pathway to the nucleus reticularis. In much the same way, others have shown that ACh-inhibited neurones of the cerebral cortex are also inhibited by MRF stimulation (Phillis & York, 1967), and it has been postulated that the ACh-inhibited neurones of the cortex function to inhibit the more deeply situated projecting pyramidal neurones (Krnjevic, 1974). Thus, analogous feed-back pathways may exist in the thalamus and cortex, in which collaterals of the projecting neurones of both structures activate a recurrent inhibitory interneurone that is itself under cholinergic inhibitory control mediated by the MRF.…”
Section: Discussionmentioning
confidence: 90%
“…Microiontophoretically applied histamine depresses the firing of feline brain and spinal neurones (Krnjevic & Phillis, 1963;Phillis, Tebecis & York, 1968a,b;Haas, Anders & Hosli, 1973); however, these effects are often non-specifically antagonized by histamine H1-and H2-receptor blockers (Phillis et al, 1968a;Haas & Bucher, 1975;Haas, Wolf & Nussbaumer, 1975). This non-specificity has been tentatively attributed either to a blockade of axonal conduction (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This non-specificity has been tentatively attributed either to a blockade of axonal conduction (i.e. a local anaesthetic effect; Reuse, 1948;Phillis et al, 1968a) or to a direct 'non-selective' action on the neuronal membrane (Haas, 1974); furthermore the ability of the antihistamines to block receptors other than the histamine receptor is well known (Goodman & Gilman, 1975).…”
Section: Introductionmentioning
confidence: 99%